MODERN METHODOLOGY OF TEACHING CHEMISTRY IN HIGHER EDUCATION - Sevinchova , Dilobar (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The modern educational process in chemistry requires innovative approaches that combine theory with practice, digital tools with traditional methods, and scientific thinking with creative problem-solving. This paper explores the evolution of chemistry teaching methodology in higher education, focusing on student-centered learning, digital platforms, and competency-based approaches. The research emphasizes the integration of interactive methods such as project-based learning, case studies, virtual laboratories, and gamified experiments. Findings suggest that these methods enhance students’ motivation, critical thinking, and professional competence, preparing them for the challenges of modern scientific and medical research.